2019
DOI: 10.1002/adfm.201900466
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Zinc Oxide Interface Instability with a Methylammonium‐Free Perovskite for High‐Performance Solar Cells

Abstract: Perovskite solar cells have achieved the highest power conversion efficiencies on metal oxide n-type layers, including SnO 2 and TiO 2 . Despite ZnO having superior optoelectronic properties to these metal oxides, such as improved transmittance, higher conductivity, and closer conduction band alignment to methylammonium (MA)PbI 3 , ZnO is largely overlooked due to a chemical instability when in contact with metal halide perovskites, which leads to rapid decomposition of the perovskite. While surface passivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(136 citation statements)
references
References 43 publications
5
131
0
Order By: Relevance
“…Such a reaction destroyed the crystal structure of the perovskite, leading to the formation methylamine and PbI 2 . [ 36,44,59 ] Due to the ZnO accelerated instability issue of the perovskite solar cells, some former works mainly focused on the removal of –OH groups on ZnO NPs through high‐temperature annealing, [ 60 ] ultraviolet ozone treating, [ 43 ] or using other base precursor substitutes. [ 59 ] Results demonstrated that decreasing the –OH groups outside the ZnO surface might be a practical approach to improve thermal stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a reaction destroyed the crystal structure of the perovskite, leading to the formation methylamine and PbI 2 . [ 36,44,59 ] Due to the ZnO accelerated instability issue of the perovskite solar cells, some former works mainly focused on the removal of –OH groups on ZnO NPs through high‐temperature annealing, [ 60 ] ultraviolet ozone treating, [ 43 ] or using other base precursor substitutes. [ 59 ] Results demonstrated that decreasing the –OH groups outside the ZnO surface might be a practical approach to improve thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…Among all of them, ZnO nanoparticles (NPs) were very popularly used in the perovskite solar cells in different device architectures. [ 27,34–36 ] You et al [ 31 ] first used ZnO as the ETL on top of the perovskite layer to replace PCBM and achieved a best efficiency of 16.1%. Bai et al [ 30 ] and Qiu et al [ 37 ] reported the use of ZnO NPs on top of the PCBM ETL to achieve a higher PCE.…”
Section: Introductionmentioning
confidence: 99%
“…During the past several years, organic-inorganic metal halide perovskite materials have attracted intensive research in the eld of solar cells owing to their strong absorption capacity, excellent defect tolerance, long carrier diffusion length and high carrier mobility. 1,2 The power conversion efficiency (PCE) record of perovskite solar cells (PSCs) has increased remarkably from 3.8% in 2009 to 25.2% recently. 3,4 The traditional construction of PSCs could be divided into planar and mesoporous structures.…”
Section: Introductionmentioning
confidence: 99%
“…1 and A 2 are pre-exponential factors and s 1 and s 2 are time constants. The detailed tting parameters are summarized inTable 1.…”
mentioning
confidence: 99%
“…Another critical issue for controlling the properties of the perovskite formulation is the selection of perovskite composition, which also affects the stability to the various degradation environments [28]. Among them, methylammonium-free (CsFA) perovskite emerges as a potential formulation for efficient and stable PVSC, as it does not incorporate the volatile methylammonium cations [28][29][30][31][32][33][34]. Michael Graetzel et al has reported that hybrid PVSCs with composition Cs 0.2 FA 0.8 PbI 2.84 Br 0.16 show a stabilized PCE of unencapsulated devices in air for more than 1000 h [35][36][37].…”
Section: Introductionmentioning
confidence: 99%